Age‐related changes of proinsulin processing in diabetic and non‐diabetic Japanese individuals. Issue 7 (17th April 2018) - Yoshino, Hiroshi; Kawakami, Kyoko; Yoshino, Gen; Hirose, Takahisa
Abstract : Aim: The present study was carried out to examine whether the insulin secretory mechanism deteriorates during the aging process using the new intact proinsulin assay system in non‐diabetic and diabetic individuals. Methods: A total of 172 participants were separated into four groups according to their age (<64 years and >65 years) and an association of type 2 diabetes; that is, 46 older diabetics (mean age 74.5 ± 6.2 years, glycated hemoglobin [National Glycohemoglobin Standardization Program] 7.5 ± 1.3%), 27 older non‐diabetics (mean age 76.9 ± 7.5 years), 48 middle‐aged diabetics (mean age 50.8 ± 10.4, glycated hemoglobin 7.8 ± 1.5%) and 51 middle aged non‐diabetics (mean age 46.6 ± 13.0 years) participants were enrolled. Results: The proinsulin/insulin (PI/I) ratio of the diabetic group was higher than that of the non‐diabetic group in the older group (0.19 ± 0.12 vs 0.11 ± 0.06, P = 0.002). In the middle‐aged groups, the PI/I ratio of the diabetic group was higher than that of the non‐diabetic group (0.16 ± 0.15 vs 0.09 ± 0.09, P = 0.003). Simple regression analysis showed that male sex (95% CI 0.02–0.01, P = 0.004), age (95% CI 0.00–0.002, P = 0.03), lower body mass index (95% CI −0.06 to 0.00, P = 0.02) and the presence of diabetes mellitus (95% CI 0.04–0.012, P < 0.0001) were significantly associated with the increase in the PI/I ratio. Multivariate regression analysis showed that male sex and age were the independent factors determining the increase in the PI/I ratio in the non‐diabetic group. After adjusted for body mass index, the PI/I ratio correlated significantly with age only in the non‐diabetic group ( r = 0.5, P = 0.004). Conclusions: The proinsulin processing system might deteriorate not only in diabetics, but also in non‐diabetic Japanese individuals with age. Also, sex‐related hormones can be protective for the proinsulin processing system.Geriatr Gerontol Int 2018; 18: 1046–1050 .